Human Coronavirus in Hospitalized Children With Respiratory Tract Infections: A 9-Year Population-Based Study From Norway. (10th November 2018) - Heimdal, Inger; Moe, Nina; Krokstad, Sidsel; Christensen, Andreas; Skanke, Lars Høsøien; Nordbø, Svein Arne; Døllner, Henrik
Abstract: Background: The burden of human coronavirus (HCoV)-associated respiratory tract infections (RTIs) in hospitalized children is poorly defined. We studied the occurrence and hospitalization rates of HCoV over 9 years. Methods: Children from Sør-Trøndelag County, Norway, hospitalized with RTIs and asymptomatic controls, were prospectively enrolled from 2006 to 2015. Nasopharyngeal aspirates were analyzed with semiquantitative polymerase chain reaction (PCR) tests for HCoV subtypes OC43, 229E, NL63, and HKU1, and 13 other respiratory pathogens. Results: HCoV was present in 9.1% (313/3458) of all RTI episodes: 46.6% OC43, 32.3% NL63, 16.0% HKU1, and 5.8% 229E. Hospitalization rates for HCoV-positive children with lower RTIs were 1.5 and 2.8 per 1000 <5 and <1 years of age, respectively. The detection rate among controls was 10.2% (38/373). Codetections occurred in 68.1% of the patients and 68.4% of the controls. In a logistic regression analysis, high HCoV genomic loads (cycle threshold <28 in PCR analysis) were associated with RTIs (odds ratio = 3.12, P = .016) adjusted for relevant factors. Conclusions: HCoVs occurred in 1 of 10 hospitalized children with RTIs and asymptomatic controls. A high HCoV genomic load was associated with RTI. HCoVs are associated with a substantial burden of RTIs in need of hospitalization. Abstract : During a 9-year period, human coronaviruses OC43, NL63, HKU1, and 229E occurred at similar rates in hospitalized children with respiratory tract infections and asymptomatic controls, but infected children had higher genomic loads, supporting a causal role in infection.